2016
DOI: 10.5539/jas.v8n4p186
|View full text |Cite
|
Sign up to set email alerts
|

Plant Density Effect on Silage Yield of Maize Cultivars

Abstract: <p>In order to study of plant density effect on silage yield of new maize hybrids an experiment was conducted in factorial on the basis of randomized completely block design with four replications at agricultural research station in Qarakheil (Qaemshahr) in 2014 in Iran, after wheat harvesting. New hybrids are SC703 and SC705 that were compared with SC704. Four densities were 75,000, 85,000, 95,000 and 105,000 plant per hectar. Eeach plant planted in four rows with intera-row spacing of 75 cm. Silage yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Adjusting row spacing is an important factor in increasing plant density [25], and modern hybrids with more upright leaf architecture allow a reduction in row spacing associated with better capture of solar radiation, which generally promotes significant increases in yield [26]. On the other hand, the nutritional value of silage can be affected by this increase in plant density [27], but it is dependent on numerous factors, including climatic conditions, plant height, and leaf area.…”
Section: Discussionmentioning
confidence: 99%
“…Adjusting row spacing is an important factor in increasing plant density [25], and modern hybrids with more upright leaf architecture allow a reduction in row spacing associated with better capture of solar radiation, which generally promotes significant increases in yield [26]. On the other hand, the nutritional value of silage can be affected by this increase in plant density [27], but it is dependent on numerous factors, including climatic conditions, plant height, and leaf area.…”
Section: Discussionmentioning
confidence: 99%
“…Shaalan et al, (2015), found that, total dry forage yield, increased from 45 to 75 days after sowing (3.18 to 8.42 t. ha -1 , respectively). As plant population density increased, total dry forage yield increased Soto et al, (2002), Widdicomble and Thelen (2002), Turgut et al, (2005), Subedi et al, (2006), Stanton et al, (2007), Carpici et al, (2010, Baghdadi et al, (2012), Karashin (2014), Haddadi and Mohseni, (2016) and Opoku (2017). With increasing density from 64,200 to 88,900 plant ha -1 , total dry forage yield increased by 1.6 t. ha -1 Ferreira et al, (2014).…”
Section: Yield and Qualitymentioning
confidence: 95%
“…On the basis of many years of research, the scientific developments and practical experience in growing maize using intensive energy-saving technology have been generalized. Much attention has been paid to improving the basic elements of technology for growing maize used for grain, silage, green fodder, as well as for food purposes and promising directions for increasing maize production in Ukraine (Chandiposha & Chivende, 2014;Haddadi & Mohseni, 2016).…”
Section: Introductionmentioning
confidence: 99%